FAKTOR FAKTOR YANG MEMPENGARUHI RETENSI PASIEN PROGRAM TERAPI RUMATAN METADON ( PTRM ) PADA PUSKESMAS KECAMATAN DI JAKARTA - , ANGLIANA DIANAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: From Data to five (5) sub-district health centers in Jakarta still visible figure out droup PTRM patients is high at 18.6% - 55.8% then it should be investigated what factors can affect the retention PTRM order numbers active customers (both survived / retention) is higher than the customer droup out, because one of the criteria for the success of methadone treatment program is the number of patients who dropped out ini the first year is less 45 % Objective : To determine the factors that will affect the retention of patient care participants Methadone maintenance therapy program in the District of Jakarta Provincial Health Center, the individual factors (age, gender, education, marital status, religion, occupation), substance factor (long life, type of drug, drug needles, disposable dose, history of detoxification) and other factors (quality of service, support) Methods : Descriptive retrospective cohort analytic design, which is a nonexperimental research approach time point approach, to look at the relationship between the independent variables and the dependent variable using statistical test Chi-Square(x2) Result and discussion : The data in this study amount to 5 487 pieces of subdistrict health centers in Jakarta. Data analysis includes univariate, bivariate and multivariate statistical tests using chi-square (x2). The results of the bivariate and multivariate analysis are: gender, occupation, marital status has a significant relationship with retention as obtained p-value <0.05, p <Ã¡, Ho is rejected it means there is a significant relationship with retention. While not significant variables are age, religion, occupation, history of other diseases, medikopsikososial factors, sexual risk factors, type of drug, drug needles, long life, disposable doses and detoxification history. While the interviews were conducted as a supporter of the Statistical test result does not affect retention. Conclusions and recommendation : There are only 3 variables of factors affecting patient retention, for drug risk factors, service factors and the interview did not affect retention. It required the involvement of all parties to expand the provision of services for prevention and treatment of drug problems, as well as integrate into health programs, education, social welfare. Keywords: PTRM, Methadone Retention